Inhibition of adaptive therapy tolerance in cancer: is triplet mitochondrial targeting the key? - Westermarck Jukka (WILEY, 2025)
Targeted therapies have become a mainstay in the treatment of cancer, but their long-term efficacy is compromised by acquired drug resistance. Acquired therapy resistance develops via two phases-first through adaptive development of nongenetic drug tolerance, which is followed by stable resistance through the acquisition of genetic mutations. Drug tolerance has been described in practically all clinical cancer treatment contexts, and detectable drug-tolerant tumors are highly associated with treatment relapse and poor survival. Thereby, novel therapeutic strategies are needed to overcome cancer therapy tolerance. Recent studies have identified a critical role of mitochondrial mechanisms in defining cancer cell sensitivity to targeted therapies and the surprising effects of established cancer therapies on mitochondria. Here, these recent studies are reviewed emphasizing an emerging concept of triplet therapies including three compounds targeting different cancer cell vulnerabilities but including at least one compound that targets the mitochondria. These mitochondria-targeting triplet therapies have very promising preclinical effects in overcoming cancer therapy tolerance. Potential strategies of how to overcome challenges in the clinical translation of mitochondria-targeting triplet therapies are also discussed.